Comprehensive identification of sensitive and stable ISFET sensing layer high-k gate based on ISFET/electrolyte models - Ahmed M. Dinar; A. S. Mohd Zain; F. Salehuddin (International Journal of Electrical and Computer Engineering (IJECE), 2019)
The ISFET sensing membrane is in direct contact with the electrolyte solution, determining the starting sensitivity of these devices. A SiO2 gate dielectric shows a low response sensitivity and poor stability. This paper proposes a comprehensive identification of different high-k materials which can be used for this purpose, rather than SiO2. The Gouy-Chapman and Gouy-Chapman-Stern models were combined with the Site-binding model, based on surface potential sensitivity, to achieve the work objectives. Five materials, namely Al2O3, Ta2O5, Hfo2, Zro2 and SN2O3, which are commonly considered for micro-electronic applications, were compared. This study has identified that Ta2O5 have a high surface potential response at around 59mV/pH, and also exhibits high stability in different electrolyte concentrations. The models used have been validated with real experimental data, which achieved excellent agreement. The insights gained from this study may be of assistance to determine the suitability of different materials before progressing to expensive real ISFET fabrication.